Strategies used to inhibit postoperative swelling following removal of impacted lower third molar - Francesco Sortino; Marco Cicciù (Wolters Kluwer Medknow Publications, 2011)
Postoperative swelling following different surgical strategies is an area of great interest. The main part of literature on the topic deals with swelling after extraction of low impacted third molar. In this review, we have analyzed publications of the last 20 years with a pubmed search using the following key words: impacted third molar, swelling third molar, wisdom tooth, edema jaw, corticosteroids and extraction third molar, antibiotic prophylaxis and tooth extraction. Attention has often been focused on corticosteroid therapy administered by diverse routes (orally, IV, IM, topically) and at different time schedules (before or after surgery or both). This investigation revealed how the use of different molecules and dosages makes the obtained results hardly comparable. Similar conclusions can be drawn from studies aimed at evaluating the efficacy of antibiotic therapy administered either before or after surgery. A complete review has also to take into account different surgical strategies used including various flaps, no traumatic osteothomy, and primary or secondary closure. The use of pharmacological therapy and application of an ice pack is critical in the postoperative period and has always provided positive results. However, even if it is difficult to come to definite conclusions, due to the variability of the design of studies analyzed, the postoperative discomfort identified with edema, pain and trismus following wisdom tooth removal is influenced by various factors such as the difficulty of the surgical procedure involved, age and gender of the patient, and experience of the surgeon. The pharmacological therapy when performed with corticosteroids seems to improve control of the postoperative swelling related with this kind of surgeries.